2010
DOI: 10.1007/s10722-010-9636-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sardinian cork oak (Quercus suber L.) genetic resources for economically important traits

Abstract: Considering the very high socio economic value of cork oak (Quercus suber L.) in Mediterranean areas, a better knowledge of local genetic resources is necessary in order to reach a good balance between the conservation issues and the need of an efficient cork production network. In such frame, local germplasm of Q. suber from the main cork production areas of Sardinia was analysed for DNA and isozyme polymorphisms and for cork quality in relation to some environmental parameters. A total number of 24 sample st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Molecular characterisation of Sardinian cork oak populations has already been assessed through RAPD markers (Bullitta et al 2011), whose results revealed a significant differentiation among populations, differently from our study. Although the sampled populations do not coincide in these two studies, a different pattern could be expected, as RAPD markers exhibit a certain lack of reproducibility due to mismatch annealing and competition for amplification among various fragments (Demeke et al 1997, Karp et al 1997.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Molecular characterisation of Sardinian cork oak populations has already been assessed through RAPD markers (Bullitta et al 2011), whose results revealed a significant differentiation among populations, differently from our study. Although the sampled populations do not coincide in these two studies, a different pattern could be expected, as RAPD markers exhibit a certain lack of reproducibility due to mismatch annealing and competition for amplification among various fragments (Demeke et al 1997, Karp et al 1997.…”
Section: Discussioncontrasting
confidence: 84%
“…Studies of the genetic and geographical structure of Q. suber have been previously reported on different populations around the Mediterranean range using different molecular markers (Magri et al 2007). First molecular characterization of Sardinian germplasm was accomplished by RAPD markers in several economically and agriculturally strategic stands (Bullitta et al 2011). However, to establish a detailed RoP map for the species, an updated and refined assessment of the genetic structure of Sardinian populations is required.…”
Section: Introductionmentioning
confidence: 99%
“…13 Cork production ranges from 150 to 5000 kg of cork per hectare every 10 years, depending on the main land use. 14 The time interval between two consecutive cork extractions is generally 10-12 years, possibly with longer intervals when adverse climate or pest infestation events occur in the year of debarking. 3 Lymantria dispar infestations can harm the health status of trees, 15,16 especially when intensive defoliation occurs after a prolonged period of drought.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural and pastoral activities in Mediterranean cork oak forests and woodlands are performed at different intensities, so that cork extraction is often coupled with other activities, such as cropping, grazing, hunting and mushroom harvesting . Cork production ranges from 150 to 5000 kg of cork per hectare every 10 years, depending on the main land use . The time interval between two consecutive cork extractions is generally 10–12 years, possibly with longer intervals when adverse climate or pest infestation events occur in the year of debarking …”
Section: Introductionmentioning
confidence: 99%